Brigada Militar e o policiamento ostensivo: uma trajetória de ressignificação institucional (1967-1988) - Simões, Moacir Almeida (2019)
The Brigada Militar, as a force for the preservation of order and public safety, was instituted in the year 1837. Due to this longevity, it went through all political-institutional phases national and of the state of Rio Grande Sul. Between 1967 and 1988, the subject of this study, it indicates another one of these remarkable stages. This period marks a period of transformations driven by the 1967 Constitution, and the specific legislation of the subsequent military police, with its repercussions in the state orbit. Of the changes brought about by this legal system, these are highlighted by means of three driving axes: personnel policy, teaching and operational systems. In the personnel part, the PM functions related to policing activity are highlighted, which starts to develop with greater intensity in a community environment, requiring a new professional position identified in this context. Associated with this change, the process of exit of quarters occurs, as an effect of the transposition of the personnel to this place of performance. Teaching, following an institutional tradition, is invested in the PM professionalization, based on the ideology established for the policing activity from 1967, based on rules and guiding principles identified with the legal basis of this period. To this end, the curriculums of institutional training courses are transformed in accordance with the new guidelines established. In the third aspect, it is verified the operational field that is the transformation of the corporation with a view to the execution of the policing activity. In this projection, the basic organization PM is changed; the policy of territorial occupation is developed, with the articulation of the troops on the ground and the territorial responsibility, in correspondence with the PM command rank. As a result of the preparatory administrative measures and the operational planning, the actual enforcement of the ostensive policing activity is verified, which became effective throughout the decade of 1970. Initially, the type of ostensible policing "general urban and rural". Then it starts to operate with other types of specialized policing, such as motorized patrol. In this process of transformation, the Brigada Militar clearly changed important identity aspects represented by the PM professionalization and the exclusive execution of the ostensive policing by means of its operational variables throughout the state.